Vinland saga. Book nine - Yukimura, Makoto, 1976- (Kodansha Comics, 2017)
"Thorfinn and his crew are on their way to Greece, the first leg of their expedition to Vinland. Having landed near Bergen, in Norway, Thorfinn is attacked by a bear, only to be saved by a fierce huntress name Hild. While sharing a meal together, Hild recounts how her village and family were massacred many years ago-- a story Thorfinn knows quite intimately. Now Thorfinn must face Hild and his own violent past in order to press forward. As his journey progresses, Thorfinn encounters more factions that do not share his vision, and a war in the name of Vinland may be looming on the horizon."--Back cover.